Izanagi-Izanami y la abertura del viaje iniciático de la vida y la muerte (El Hilo de la Fabula, 2022)
Travel, as a spatial, temporal or mental displacement, has been a literary topic in the universal narrative. Studied at various times, "travel literature" has been mutating until trying to become a literary subgenre in both European and American literature, but the treatment of this topic in many Asian literatures is still ignored. For this reason, in this work I will try to provide an approach to this topic in a particular culture such as the Japanese one. Thus, I will consider the trip as one of the obturator points in the Japanese cosmogonic myths that are compiled in the Kōjiki and the Nihonshoki. Focused on the first mythological cycle of Yamato, starring the primordial couple Izanagi-Izanami, I will reveal the displacement under two aspects: the journey-creator-of-life and the journey-generator-of-death. In both types of trips, the concept of beauty will be the connecting and triggering link.
Keywords: Izanami; Izanagi; journey-of-life; journey-of-death; beauty